2020
DOI: 10.30564/jasr.v3i4.2342
|View full text |Cite
|
Sign up to set email alerts
|

Corona with Streamers in Atmospheric Pressure Air in a Highly Inhomogeneous Electric Field

Abstract: The paper presents research data on positive and negative coronas in atmospheric pressure air in a highly inhomogeneous electric field. The data show that irrespective of the polarity of pointed electrodes placed in a high electric field (>200 kV/cm), this type of discharge develops via spherical streamers even if the gap voltage rises slowly (£0.2 kV/ms). The start voltage of first positive streamers, compared to negative ones, is higher and the amplitude and the frequency of their current pulses are much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 34 publications
3
19
0
Order By: Relevance
“…An increase in U DC , in this case, will lead to a gap breakdown [33] . The data are in agreement with the results obtained with corona and diffuse discharges from a metal tip [29,34] , as well as with an apokampic discharge from a positive charged bent plasma channel between two pointed electrodes [28] . When a pointed electrode is a cathode (a negative tip) electrons move to a region where an electric field strength is lower, i.e.…”
Section: Characteristics Of the Discharge Implemented Between Additio...supporting
confidence: 89%
See 4 more Smart Citations
“…An increase in U DC , in this case, will lead to a gap breakdown [33] . The data are in agreement with the results obtained with corona and diffuse discharges from a metal tip [29,34] , as well as with an apokampic discharge from a positive charged bent plasma channel between two pointed electrodes [28] . When a pointed electrode is a cathode (a negative tip) electrons move to a region where an electric field strength is lower, i.e.…”
Section: Characteristics Of the Discharge Implemented Between Additio...supporting
confidence: 89%
“…Preliminary experiments have shown that such a discharge are red colored due to the emission of bands formed by spectral transitions of the 1+ system of a nitrogen molecule and are can be classified as a streamer discharge. This paper, unlike others dealing with laboratory modeling of red sprites in low-pressure air [15,[26][27][28][29][30][31] , has a significant difference in the form of an electrodeless discharge.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations